Pembiayaan Pada Bank Syariah - Randa R; Nurul Huda; Nola Fibriyani Bte Salam; Nurnasrina N (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines Islamic bank financing as a vital tool in supporting sustainable economic growth and social justice. Islamic bank financing operates based on Islamic principles, such as the prohibition of usury, clarity of contracts and ethics in transactions. Various financing products including murabahah, ijarah, musyarakah and mudharabah are outlined to show how each type of financing meets the needs of customers despite the challenges of Islamic banking. Using a qualitative method of analysis, this study concludes that despite the challenges, the growth of Islamic bank financing shows significant potential in driving economic growth.